(untitled) (INTERNATIONAL SEMINAR, 2024)
Agency performance describes the results of efforts achieved by employees, seen from the quality and quantity in carrying out their obligations. Performance describes the entire work process. Agency performance measurement needs to be done so that the achievement of employee work results can be known and evaluated further. This study aims to determine the effect of the application of accounting information systems and the quality of financial reports on the performance of government agencies in the Regional Government Organization of Trenggalek Regency. This research is a quantitative research with an explanatory approach. The sampling technique used was saturated sampling with a population of 40 respondents. The primary data used was collected through a questionnaire survey. The analysis method used in this study is a validity test, reliability test, multiple linear regression, and t-test statistical test. Hypothesis testing is done using SPSS for Windows Software. The results of this study indicate that the influence of the application of accounting information systems and the quality of financial reports simultaneously and partially have a positive and significant effect on the performance of local government agencies. Based on these results, it is expected that the Regional Apparatus Organization, under the auspices of the Regional Finance Agency of Trenggalek Regency, will pay more attention to these issues to improve its performance.